Analisis Cara Kerja Fire Alarm System di Gedung Nusantara I DPR RI - Enjel Rosiana; Mohammad Fatkhurrokhman (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
A fire alarm system is an automatic early detection system for the danger of fire by looking at the stages of changes in surrounding environmental conditions before fire or smoke triggers a fire. The way a fire alarm works is as a fire detection system used in buildings, the fire system uses conventional fire detection sensors such as smoke sensors or heat sensors. These sensors are placed in various locations within the building, depending on the need and type of hazard to be detected. Research into how fire alarms work is carried out to improve public safety. Fire alarm systems are a key component in preventing fires and providing early warning to building occupants, which can save lives. This research was carried out to reduce reaction time to fire. The sooner a warning is given, the sooner preventative or evacuation action can be taken, so that the risk of injury or death can be minimized. This research method was carried out in two stages. The first stage is direct observation and interviews with officers and staff at the research site and the second is by searching for literature such as journals related to the problem being discussed. How a fire alarm system works is very important in maintaining security and safety in various types of buildings and environments. In carrying out this analysis, we can conclude that fire alarm systems are designed to detect fires as soon as possible. This allows for precautionary measures and rapid evacuation, reducing the risk of damage and loss of life.